Late Quaternary paleosols and landscape evolution in dune systems of Veracruz at the Gulf of Mexico coast. (30th April 2022) - Solleiro-Rebolledo, Elizabeth; Sedov, Sergey; Terhorst, Birgit; López-Martínez, Rafael; Díaz-Ortega, Jaime; Díaz-Hernández, Yusnier; Valera-Fernández, Daisy; Cabadas-Báez, Héctor; Tsukamoto, Sumiko
Abstract: The Gulf of Mexico coastal plain contains one of the largest dune systems in Mexico. These dunes and particularly their paleosols contain valuable paleoenvironmental information, however this aspect has been poorly studied. Here, we present the preliminary results obtained from buried paleosols of coastal dune ridges in Veracruz with the aim to reconstruct the environmental conditions during their formation as well as the phases of stability (pedogenesis) and instability (sedimentation) of the landscape. Three profiles were studied in the areas of Punta Delgada, PD (in the north), Palma Sola, PS, and La Mancha, LM (in the south). The chronological frame was constructed by radiocarbon dating of paleosols organic matter and pedogenic carbonates, and by Optical Stimulated Luminiscence (OSL) dating for the dune sediments. For each section several paleosols levels were identified whose properties permitted the differentiation of pedogenetic trends as well as their periods of formation. Nevertheless, the three sections did not provide for a continuous record of pedogenesis and sedimentation, as most of the paleosols are truncated by erosion. PS is the most complete profile which is formed from Marine Isotope Stage (MIS) 5c to MIS 1, with especially well-developed Holocene paleosols. LM includes only paleosols developed during MIS 4 and MIS 3, and PD shows only one paleosol originated during MIS 2. Although, the chronology is not complete as it has been constructed with a few dates, we consider each section contains information from different chronological windows. The results demonstrate that the oldest paleosols formed under more humid conditions during MIS 5c to 5a and probably MIS 4. As the MIS 4 to MIS 2 paleosols contain pedogenic carbonates, we interpret drier climates or with higher evapotranspiration rates. Paleosols from the early Holocene exhibit vertic properties probably formed by seasonal climates. Soils from the Middle-Late Holocene are less developed, due to the activation of the dune sedimentation. The results found here are compared at a regional scale with the dune system in the northern Gulf of Mexico and Yucatan peninsula, revealing both synchronous and asynchronous systems of eolian dynamics. The major asynchrony relates to the Wisconsinian stage (MIS 4 to MIS 2) for which high intensity of dune development is documented in the Veracruz and northern coasts whereas no dunes of that age are found in the Yucatan peninsula.